Zooantroponózne dermatomykózy u mestského obyvatel'stva - Simaljaková, M; Polák, I (Epidemiologie, mikrobiologie, imunologie, 1995)
The authors analyzed epidemiologically two cases of trichophytosis caused by zoophilic dermatophytes in persons living in the city. The first case was a male aged 43, suffering from trichophytosis on the right side of his neck. The patient was infected at work from guinea pigs. Trichophyton mentagrophytes varietas granulosum was the etiological agent. The second case occurred in a female aged 29, suffering from trichophytosis on her left arm. Trichophyton verrucosum was the causal agent. A horse was the source of infection.
Keywords: Urban Health; tinea; Zoonoses; Female; Adult; dospělí; Tinea; Animals; Humans; ženské pohlaví; mužské pohlaví; zdraví ve městech; lidé; zoonózy; Male; zvířata